OPTIMASI DISTRIBUSI ROTI MENGGUNAKAN MODEL STEPPING STONE (Studi Kasus: Pabrik Roti Gedangan, Asahan) - Cici Padillah; Egi Adelia; Andy Sapta (Smart Education, 2018)
Abstract: This study aims to solve the problem of transportation costs for Bagus Bakery and Early Bakery producers by using the Stepping Stone model transportation method. The first step in completing the minimum transportation costs is to form the distribution costs, the amount of production and demand into the transportation model. Furthermore, the transportation model was analyzed using the stepping stone model. The application of the distribution transportation model using the stepping stone model can provide a solution for bakeries in optimizing bread distribution costs of 68,550 IDR. Thus in the calculation process using the Stepping Stone it turns out that it can minimize transportation costs with a difference in costs of 81,450 IDR. Keywords: transportation method, stepping stone Abstrak: Penelitian ini bertujuan untuk menyelesaikan permasalahan biaya transportasi produsen Bagus Bakery dan Dini Bakery dengan menggunakn metode transportasi model Stepping Stone. Langkah pertama dalam menyelesaikan biaya transportasi yang minimum adalah membentuk biaya pendistribusian, jumlah produksi dan permintaan kedalam model transportasi. Selanjutnya model transportasi dianalisis menggunakan model stepping stone. Penerapan model transportasi distribusi dengan menggunakan model stepping stone dapat memberikan solusi pada toko roti dalam pengoptimalan biaya distribusi roti sebesar Rp 68.550. Dengan demikian pada proses perhitungan dengan menggunakan Stepping Stone ternyata dapat meminimumkan biaya transportasi dengan selisih biaya sebesar Rp 81.450. Kata kunci: metode transportasi, stepping stone